International perspectives on early childhood education and care - Georgeson, Jan; Payler, Jane (McGraw-Hill, Open University Press, 2013)
"This book discusses key influential approaches to ECEC across the world, considering less well-known systems to broaden thinking." -- Resumé vydavatele
Keywords: předškolní výchova -- mezinárodní kontext; preschool education -- international context; kolektivní monografie; elektronické knihy; collective monographs; electronic books